Periodic tiling of triangular and square nanotubes in a cationic metal–organic framework for selective anion exchange1. Issue 46 (11th June 2015) - Song, Bai-Qiao; Wang, Xin-Long; Zhang, Yu-Teng; Wu, Xue-Song; Liu, Hong-Sheng; Shao, Kui-Zhan; Su, Zhong-Min
<x xml:space="preserve">Abstract</x> A unique cationic metal–organic framework formed by connecting the neutral chain-like secondary building units with positively charged ligands shows charge- and size-dependent ion-exchange of anion dyes.